First fossil Micropholcommatidae (Araneae), imaged in Eocene Paris amber using X-Ray Computed Tomography - Penney, David; Dierick, Manuel; Cnudde, Veerle; Masschaele, Bert; Vlassenbroeck, Jelle; van Hoorebeke, Luc; Jacobs, Patric (Zootaxa, 2007)
We apply Very-High-Resolution X-Ray Computed Tomography (VHR-CT) to a minute fossil spider ( 1 mm long) from Eocene amber of the Paris Basin, France. We demonstrate that the newly described genus and species of Micropholcommatidae, Cenotextricella simoni, retains excellent details of the somatic and male pedipalpal morphology that allows unqualified comparison with extant species. Thus, in addition to calibrating the tree of life, such fossils can now be incorporated into cladistic matrices and their resultant phylogenies. This is the first fossil record of the family Micropholcommatidae, extending the known geological range of the family by 53 million years (lowermost Eocene) and that of the symphytognathoid clade by approximately 5–9 million years.